Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1177/1403494807086980
|View full text |Cite
|
Sign up to set email alerts
|

The significance of policy documents in municipal child health promotion

Abstract: This study shows that policy documents are present in policy processes related to child health-promoting activities in Swedish municipalities. As Swedish municipalities are autonomous and not forced to pursue governmental recommendations, this probably demonstrates that policy documents are significant in the development of such processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…Since the 1980s, these core members have initiated health-promotion activities and driven them forwards, at the outset principally in the form of ad-hoc measures at departmental level in a decentralized and sectorally divided administration. This kind of engagement, combined with a position of power based on professional knowledge, has been shown to be of importance in health-development processes [29]. …”
Section: Discussionmentioning
confidence: 99%
“…Since the 1980s, these core members have initiated health-promotion activities and driven them forwards, at the outset principally in the form of ad-hoc measures at departmental level in a decentralized and sectorally divided administration. This kind of engagement, combined with a position of power based on professional knowledge, has been shown to be of importance in health-development processes [29]. …”
Section: Discussionmentioning
confidence: 99%
“…asked whether the packages would increase quality of health promotion, 38% answered that this was likely to a high extent, while 55% thought the likelihood was only moderate [2]. a Swedish study showed that similar policy documents were used by municipalities in child-health promotion [3].…”
Section: Introductionmentioning
confidence: 99%
“…As such, the primary focus is on introducing and managing change within organizations and/or whole systems (Dooris 2006). Settings-based HP activities provide a way of influencing local community behaviour and/or the development of health-promoting practices (Guldbrandsson, Back, and Bremberg 2008;Hawe, Wise, and Nutbeam 2001). For example, Bormann and Stone (2001) reported that a policy banning alcohol in American college-sporting stadiums reduced arrests and assaults at the venue.…”
Section: Introductionmentioning
confidence: 99%